Detecting Earnings Management through Compliance of Audit Committee’s Related Rules - Mohammad Taufiq JUDHANTO; Siti NURYANAH (Communications of International Proceedings, 2020)
This study primarily aims to investigate the determinant of company’s compliance with audit committee rules. This study also examines the association of effectiveness components of audit committee, which are composition, authority, resources, and diligence with earnings management. Using 562 listed companies in Indonesia Stock Exchange (IDX) as a sample, the result shows that board of commissioner characteristics, company’s size and listing age are found to be significant factors for company’s compliance with audit committee rules. Additionally, the authority is positively associated, and the size of audit committee is negatively associated with earnings management. However, this study fails to find the association between audit committees’ expertise and meeting frequencies with earnings management.
Keywords: audit committee effectiveness; expertise; authority; size; diligence; discretionary accruals; and company’s compliance.